Tamil-Brahmi (Tamili) Pottery Shards of Tamil Nadu A Study - Rajavelu, S.; Saravankuamar, AR.; Paranthaman, G.; Paranthaman, S.; Murugan, P. (International Journal of Psychosocial Rehabilitation, 2020)
Recent Archaeological excavated site at Kīladi brought to light several ways of ancient Tamils cultural history. The most important findings at Kīladi are inscribed pot-shreds. The findings of the archaeological excavated site Kīladi significantly revealed a new chapter in the archaeological context where a large number of brick structures along with antiquities have been unearthed which attracted the public as well as the academic forum. Especially the date of Tamili or Tamil Brahmi script has been arrived at the 6th century BCE based on AMS dates. It gives the clue that the Tamili is the earliest known script in India which was prevalent amidst the people of Tamil Nadu as people`s script. The scientific data arrived at by the Department of State Archaeology, Government of Tamil Nadu for the Tamili script through an analysis at Beta analytical center at Florida, The United States of America voiced the opinion of many renowned scholars and changed the view on the origin and writing system of Tamili script (Tamil script) as well as its authorship. The AMS dates from three excavated sites namely Porunthal, Kodumanal, and Kīḻaḍi significantly fixing the date of Tamili script to the 6th century BCE which is the earliest date for an Indian script used by the common folk of Tamil Nadu, the southern part of the Indian Sub-continent. Hence, the topic literacy of the Ancient Tamilagam has been taken in the academic forum.